AGRICULTURAL REFORMS IN SERBIA - Jevtić, Stojan; Gulan, Branislav; Stanković, Vojislav (Economics of Agriculture, 2018)
After half a century of wandering and neglecting, in 2009 the agriculture in Serbia is again on the crossroads. How and where to proceed? The science created about 1,500 high-yielding varieties and hybrids, and only 30% of its genetic potential is used. Every fourth Serbian village is heading towards extinction (about 1,200 of them). In the Serbian villages, there are 260,000 single men, who entered their fifth decade without having created their own families. In the same time, there are 200,000 empty homes in the villages, and 600,000 hectares of arable land remain uncultivated! Before the crisis, a GDP growth in Serbia for 2009 was projected at 7%, then it was planned at 3.5%, and now, with the reality check we have a drop of more than 5%, and in agriculture, we can expect a zero rate. The State has still not recognized that agriculture is its strategic sector of economy. After elaboration of each new strategy, the production was reduced.